INVENTORY OF SEAGRASS SPECIES AND THEIR ASSOCIATIONS WITH GASTROPODS IN BEACHES OF POKA, AMBON CITY, MALUKU PROVINCE - Rumpeniak, Yusuf; Hiariej, Adriana; Sahertian, Dece Elisabeth (Universitas Pattimura, 2019)
This study aims to determine the types of seagrass and their association with gastropods in the coastal waters of Poka Village, Ambon Bay District, Ambon City, Maluku Province. The laying of transect lines was based on the presence of seagrass beds, seagrass and gastrooda samples were taken from the same transect, using the 1×1 m quadrant transect method. Sample identification was carried out by LIPI Ambon's Marine Biota Conservation Agency Laboratory. Three species of seagrass were found namely Enhalus acoroides, Holophila ovalis, Halodule uninervis. Ten species of gastropods were found, namely Polinices mammilla, Natica vitellusi, Strombus labiatus, Strombus urceus, Bursa tuberosissima, Liotina peronii, Conus coronatus, Conus moriculatus, Nassarius pullus, Nassarius limnaeiformis. There is a positive association between seagrass and gastropods which means that the species These tend to be found together in each observation plot and show tolerance for living together or there is a mutually beneficial reciprocal relationship.